MODERN EDUCATIONAL METHODS IN TEACHING ENGLISH (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines major trends and strategies in contemporary English language education, including technology integration, blended learning, taskbased learning, project-based learning, and gamification. Using these modern methods, teachers can create a dynamic and effective language learning environment that meets the diverse needs and preferences of students, ultimately empowering them to communicate confidently and effectively in English.